INOVASI DIGITAL UNTUK DETEKSI DINI PERKEMBANGAN ANAK USIA PRASEKOLAH - Anik Enikmawati (Jendela Nursing Journal (JNJ), 2026)
Background: Early detection of growth and developmental milestones in preschool children is a crucial effort to improve the quality of human resources from an early age. The implementation of Early Stimulation, Detection, and Intervention of Child Growth and Development (SDIDTK) in Indonesia is still commonly conducted using paper-based forms, which is time-consuming and less efficient, particularly for parents with limited time and access Purpose: This study aims to develop a digital innovation in the form of an Android-based application that enables practical, fast, and accurate early detection and intervention of preschool children’s growth and development. Methods: The research employed a Research and Development (R&D) design, consisting of preliminary studies, application design, interface development, and a limited trial involving preschool children, teachers, and parents. The application, named DDTKA (Deteksi Dini Tumbuh Kembang Anak), is equipped with features such as child data management, age-specific screening, interpretation of growth and developmental status, and recommendations for follow-up actions Results: Results of the limited trial indicated that the application was feasible to use, well accepted by users, and has the potential to improve efficiency in growth and developmental screening Conclusion: This innovation is expected to provide an applicable digital solution to support parents, teachers, and health workers in monitoring and intervening in preschool children’s growth and development